Adolescent Opiate Exposure in the Female Rat Induces Subtle Alterations in Maternal Care and Transgenerational Effects on Play Behavior - Johnson, Nicole L.; Carini, Lindsay; Schenk, Marian E.; Stewart, Michelle; Byrnes, Elizabeth M. (Frontiers in Psychiatry, 2011)
The non-medical use of prescription opiates, such as Vicodin® and MSContin®, has increased dramatically over the past decade. Of particular concern is the rising popularity of these drugs in adolescent female populations. Use during this critical developmental period could have significant long-term consequences for both the female user as well as potential effects on her future offspring. To address this issue, we have begun modeling adolescent opiate exposure in female rats and have observed significant transgenerational effects despite the fact that all drugs are withdrawn several weeks prior to pregnancy. The purpose of the current set of studies was to determine whether adolescent morphine exposure modifies postpartum care. In addition, we also examined juvenile play behavior in both male and female offspring. The choice of the social play paradigm was based on previous findings demonstrating effects of both postpartum care and opioid activity on play behavior. The findings revealed subtle modifications in the maternal behavior of adolescent morphine-exposed females, primarily related to the amount of time females’ spend nursing and in non-nursing contact with their young. In addition, male offspring of adolescent morphine-exposed mothers (MOR-F1) demonstrate decreased rough and tumble play behaviors, with no significant differences in general social behaviors (i.e. social grooming and social exploration). Moreover, there was a tendency toward increased rough and tumble play in MOR-F1 females, demonstrating the sex-specific nature of these effects. Given the importance of the postpartum environment on neurodevelopment, it is possible that modifications in maternal-offspring interactions, related to a history of adolescent opiate exposure, plays a role in the observed transgenerational effects. Overall, these studies indicate that the long-term consequences of adolescent opiate exposure can impact both the female and her future offspring.